Where is the “History” in Translation Histories? - Malena, Anne (TTR)

(untitled) (Association canadienne de traductologie, 2011)
This paper explores two interrelated problems of method of concern to translation historians and that are part of the overarching issue of interdisciplinarity. The first has to do with conflicting methods used in history and the second with deciding whether or not it is necessary for a translation scholar to define her or his philosophical position with regards to history. This article is part of a book project on the history of translation in Louisiana, which has been understudied. The writing of a translation history implies the act of rendering visible what has been obscured by the official grand narrative of History, or what Nietzsche called “monumental” history. To look for translation where officially there was none, or very little, amounts to search for multiple histories of people who do not necessarily fit into the dominant definition of what it means to be American, because they spoke languages other than English and adhered to cultural practices that resisted melting into the common pot. From this perspective history is viewed as discourse because, very much like translation, it is made up of language, seen as living matter shaped and manipulated by power relations. The focus of the study is two local 19th-century historians from Louisiana who repeatedly doubled up as translators—from French to English and back into French—to produce histories of Louisiana. The conclusion states that translation historians are first historiographers, imbued with all the disciplinary and ethical responsibilities that entails. Since historiography forms a nexus for history and translation, it is not only necessary to theorize both but also to develop methods that can be integral to both.